2012
DOI: 10.1111/j.1557-9263.2011.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Demography and population trends of Whooping Cranes

Abstract: Previous studies of Whooping Crane demography used estimates of fecundity rates based on females in captivity, and breeding success was estimated based on either the number of unbanded pairs nesting or the number arriving in wintering areas with chicks. We analyzed demographic data from 12 cohorts of banded Whooping Cranes (Grus americana) from the Aransas National Wildlife Refuge/Wood Buffalo National Park (ANWR/WBNP) population that had not been compiled previously into a single data base and had not been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…1.Ranges of the Mid-continent and Rocky Mountain populations of sandhill cranes in North America and AWBP whooping cranes. Ranges shown include breeding, winter and migration routes (Gil-Weir et al 2012; Krapu et al 2011). Locations where sandhill cranes included in this study were harvested are indicated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1.Ranges of the Mid-continent and Rocky Mountain populations of sandhill cranes in North America and AWBP whooping cranes. Ranges shown include breeding, winter and migration routes (Gil-Weir et al 2012; Krapu et al 2011). Locations where sandhill cranes included in this study were harvested are indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Ranges shown include breeding, winter and migration routes (Gil-Weir et al 2012; Krapu et al 2011). Locations where sandhill cranes included in this study were harvested are indicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the tools and technology of modern wildlife management, we would like to believe we could detect population declines as steep as the passenger pigeon experienced and intervene before it is too late. Given some caveats, we have repeatedly demonstrated that capability on smaller scales in time and space with several threatened and endangered species (e.g., California condors [ Gymnogyps californianus ; Meretsky et al , Walters et al , Finkelstein et al ], bald eagles [ Haliaeetus leucocephalus ; Bowerman et al , Watts et al , Mougeot et al ], whooping cranes [ Grus americana ; Cannon , Gil‐Weir et al , Butler et al ], and gray wolves [ Canis lupus ; Mech , Ripple et al , Treves et al ]).…”
Section: Have We Learned Our Lesson(s)?mentioning
confidence: 99%
“…Ключевые слова: осенние предотлетные скопления; число птиц в стаях; сроки гнездования; поведение птиц Введение Все три вида журавлей находятся под охраной как на международном, так и государственном уровнях в России и большинстве стран, входящих в ареалы этих птиц (Higuchi et al, 2004;Marsh and Trenhan, 2008;Yuxiang et al, 2012;Gilber et al, 2016;Heim and Suanjak, 2016;Butler, 2017). Численность всех из них низка, имеет тенденцию к снижению, а наиболее многочисленный черный журавль относится к наименее изученным видам Палеарктики (Gil-Weir et al, 2012;Liying and Hongfei, 2012;Butler, 2013;Wang et al, 2014;Sun et al, 2015;Gilber et al, 2016;Zhou et al, 2016).…”
unclassified